Synthesis of new benzothiazole derivatives with in-depth In-vitro, In-vivo anti-oxidant, anti-inflammatory and anti-ulcer activities - Ayesha Khan; Neelum Gul Qazi; Arooj Mohsin Alvi; Safia Obaidur Rab; Kashif Iqbal; Humaira Nadeem (PLoS ONE, 2026)
Benzothiazoles (BTZ) possess various medicinal benefits and in this study, we have synthesized benzothiazole derivatives by substituting its side chains, and analyzed its spectral analysis along with its antioxidant and anti-inflammatory activity. In-vitro antioxidant activity of the benzothiazole derivatives indicated strong antioxidant potential of 3b , 3d and 3e which were then evaluated for their anti-inflammatory potential in mice’s paw edema and ethanol-induced gastric ulcer (GU). The compounds demonstrated strong anti-inflammatory ability in paw edema as well as ethanol-induced gastric ulcer. This was further confirmed by H&E staining and suppressed inflammatory mediators as tumor necrotic factor (TNF-α), nuclear factor B (p-NFkB), and cyclooxygenase-2 (COX-2). The antioxidant ability was assessed by measuring catalase (CAT), glutathione-S-transferase (GST), glutathione (GSH), superoxide dismutase (SOD), and lipid peroxidation (LPO) levels in both edema and ulcer models. Additionally, gastric lesions were detected in the ulcer and low Ulcer index confirmed anti-ulcer ability. These results suggest new benzothiazoles which can be further analyzed through clinical studies.